Analyzing the evolutionary game of subsidies’ strategy in the digitization of marine ranch: a theoretical framework - Zheng, Shan; Zhang, Ying (Frontiers in Marine Science, 2024)
This study establishes a three-party evolutionary game model that includes marine ranch firms, consumers, and the government, with a focus on the digital transformation pattern of marine ranching. Subsequently, the researchers conduct gaming and simulation to analyze the government subsidy strategy in the digital transformation of marine ranching. The following findings are derived: (1) Government subsidies have the potential to facilitate the digital transformation of marine ranches, benefiting both the supply and demand sides. Government subsidies positively influence both the digital transformation of marine ranch firms and the involvement of consumers in this transformation process. (2) The findings from the evolutionary game system demonstrate that alterations in the cost–benefit dynamics of each participant lead to adjustments in the steady state, thereby prompting the government to adapt its optimal subsidy strategy. (3) More government subsidies are not always better. Excessive government subsidies will destroy the stability of the evolutionary game system, which is not conducive to the realization of the digitization of marine ranch. (4) Subsidizing consumers is more effective in driving the digital transformation of marine ranch than subsidizing marine ranch firms. Subsidies to marine ranch firms will destroy the stability of the evolutionary game system, whereas subsidizing consumers contributes positively to its stability.